2009
DOI: 10.1021/ja906356g
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneously Catalyzed Asymmetric Hydrogenation of C═C Bonds Directed by Surface-Tethered Chiral Modifiers

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…The hydrogen under potential deposition (H UPD , ca. 34 The isolation of free Pt sites by the ligands is in agreement with the absence of any catalytic CO oxidation activity. In addition, no CO oxidation was detected during a CO stripping cycle, so it can be assumed that the complete Pt surface is blocked and no ECSA can be determined for fresh NA-Pt NP samples.…”
Section: Resultssupporting
confidence: 61%
“…The hydrogen under potential deposition (H UPD , ca. 34 The isolation of free Pt sites by the ligands is in agreement with the absence of any catalytic CO oxidation activity. In addition, no CO oxidation was detected during a CO stripping cycle, so it can be assumed that the complete Pt surface is blocked and no ECSA can be determined for fresh NA-Pt NP samples.…”
Section: Resultssupporting
confidence: 61%
“…This conclusion that adsorption is non-dissociative is strongly confirmed by the NEXAFS data presented in Figure 2. In our earlier work 11 we proposed a mechanism for the asymmetric hydrogenation of isophorone (1) which involved interaction between the secondary amine of the chiral modifier 2 and the ketone functionality of the enone to yield an iminium species (4) (or enamine) as the reaction intermediate (Scheme 2). In keeping with this we found that, when used as the chiral agent, a tertiary amine analogue of 2 which prevents formation of such an intermediate gave only racemic product.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This goal has now been achieved 79 by purposeful synthesis of chiral ligands that contain the 400 characteristic pyrrolidine motif present in proline, anchor robustly to the metal surface, resist 401 displacement and direct the heterogeneously-catalyzed enantioselective hydrogenation of isophorone, as 402 described below. 403…”
mentioning
confidence: 99%
“…79 Each 404 contained a sulfur atom in order to achieve covalent tethering to the metal surface. The result of using 405 these chiral sulfide ligands as chiral modifiers in the Pd/C-catalyzed hydrogenation of isophorone is 406 summarized in Figure 7, which shows the measured e.e.…”
mentioning
confidence: 99%